Pegylated liposomal doxorubicin in ovarian cancer - Robert Strother; Daniela Matei (Dove Medical Press, 2009)
Robert Strother1,2, Daniela Matei1–51Department of Medicine, 2Indiana University Melvin and Bren Simon Cancer Center, 3Department of Obstetrics and Gynecology, 4Department of Biochemistry and Molecular Biology, 5VA Roudebush Hospital Indiana University School of Medicine, 535 Barnhill Drive, Indianapolis, IN, 46202Abstract: The encapsulation of doxorubicin in a pegylated liposomal matrix led to a reformulated agent with a different toxicity profile and improved clinical utility. Liposomal doxorubicin is devoid of the cardiac toxicity associated with doxorubicin, but is associated with predictable muco-cutaneous toxicity. The liposomal formulation leads to improved delivery to the target tumor tissue, allowing enhanced uptake by cancer cells. These properties translate into clinical utility in recurrent ovarian cancer as demonstrated by phase II and III trials, this proven clinical efficacy leading to FDA approval in second-line therapy for ovarian cancer. New combinations with cytotoxics, in particular with carboplatin, have demonstrated an acceptable toxicity profile and clinical utility in platinum-sensitive ovarian cancer. A favorable toxicity profile renders liposomal doxorubicin an ideal partner for combination regimens with other cytotoxics, and more recently with biological agents. Such combinations are the subject of ongoing clinical trials.Keywords: ovarian cancer, doxorubicin, liposomes, pegylated liposomal doxorubicin